2020
DOI: 10.29010/88.11
|View full text |Cite
|
Sign up to set email alerts
|

Кинетика Деформаций При Однопроходной Сварке Плавлением Симметричного Стыкового Соединения

Abstract: В работе представлены результаты кинетики температуры и осевых деформаций, влияющих на формирование временного и остаточного напряжённо-деформированного состояния сварного соединения.Установлены принципиальные отличия в характере распределения остаточных продольных пластических деформаций в сравнении с приближенными инженерными методами.Результаты конечно-элементного моделирования связанной задачи термо-упруго-пластичности в симметричном стыковом соединении 600х240х10 мм из стали 08пс представлены для … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The issue is complicated by a significant decrease in the strength characteristics and stresses in the area of the thermal influence of the welded joint [1,2]. It is impossible or difficult to fully define the properties of a welded joint's metal without its destruction.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The issue is complicated by a significant decrease in the strength characteristics and stresses in the area of the thermal influence of the welded joint [1,2]. It is impossible or difficult to fully define the properties of a welded joint's metal without its destruction.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Numerous studies have shown that due to the variability of product quality indicators, there are no absolutely effective methods to prevent non-conformities [1][2][3][4]. The inability to prevent non-conformities leads to the need to identify non-conformities using product quality inspection methods.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%